Một trăm linh một 101 smart questions to ask on your interview - Fry, Ron (Course Technology, 2009)
This book is for every job candidate who thinks "Do you have any questions for me?" marks the end of an interview. In the author's view, it marks the beginning of the last and perhaps most important interview phase - a phase so important that failing to prepare properly for it can undo all your hard work, including providing great answers to tough questions! It's your moment to shine - to show off the depth and breadth of your research, to remind the interviewer of how perfectly your credentials fit the job description, and to actually ask for the job! From what to ask, when to ask it, and the kind of answers to expect, this book gives every candidate, from first-timers to seasoned pros, the practical information and advice they need to ace the entire interview and get their dream job